Bibliometric Study of Multicultural-based Islamic Education Learning Models in Public Schools - Judijanto, Loso; Rusdi, Muhammad (West Science Interdisciplinary Studies, 2024)
This bibliometric analysis explores the evolving landscape of Islamic education research, emphasizing the integration of traditional Islamic values with modern educational technologies and methodologies. Utilizing VOSviewer, the study analyzes key themes and trends in the literature from 2016 to 2021, highlighting a significant shift towards student-centered learning, the application of digital tools, and the response to global challenges such as the COVID-19 pandemic. The findings reveal a robust engagement with both traditional elements of Islamic education and contemporary pedagogical practices, demonstrating a dynamic field that is adapting to meet the needs of diverse, modern student populations. The analysis also identifies future research directions, including the empirical assessment of technology integration in Islamic education, the promotion of intercultural competence, and the enhancement of student well-being.